2023
DOI: 10.1039/d3ra00434a
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow diffusion barrier induced by intercalation in layered N-based cathode materials for sodium-ion batteries

Abstract: Layered 2H-phase CrN2 with Cs intercalation possesses many advantages including an ultra-low diffusion barrier (0.04 eV), high voltage platform (3.9 V), and high energy density (903 W h kg−1), and is a promising candidate for SIB cathode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The outcomes illustrate a significant decrease in the diffusion barrier with an increase of d 002 . A larger d 002 will facilitate Na diffusion between interlayers, resulting in an improved rate capability of HCs. , Based on the calculation outcomes, it can be concluded that dual-functionalized Ca with interlayer Ca 2+ to widen the d 002 and in situ CaSe templates to create hierarchical pore structures and induce intrinsic defects can thermodynamically and dynamically facilitate Na + storage and transport, contributing to excellent sodium storage performance.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes illustrate a significant decrease in the diffusion barrier with an increase of d 002 . A larger d 002 will facilitate Na diffusion between interlayers, resulting in an improved rate capability of HCs. , Based on the calculation outcomes, it can be concluded that dual-functionalized Ca with interlayer Ca 2+ to widen the d 002 and in situ CaSe templates to create hierarchical pore structures and induce intrinsic defects can thermodynamically and dynamically facilitate Na + storage and transport, contributing to excellent sodium storage performance.…”
Section: Resultsmentioning
confidence: 99%